Optimization of electrical stimulation for the treatment of lower limb dysfunction after stroke: A systematic review and Bayesian network meta-analysis of randomized controlled trials. - Yu Fang; Jiang Li; Shanyu Liu; Yan Wang; Jiaming Li; Dongdong Yang; Qiaoling Wang (PLoS ONE)
Objective To compare the treatment effect of five electrical stimulation methods commonly used in the treatment of stroke patients with lower limb dysfunction. Methods We implemented a systematic search of 3915 studies published up to January 2023 from eight databases and two clinical trial registries. First, two independent reviewers critically evaluated trial eligibility according to the inclusion and exclusion criteria. Next, they selected and extracted data. Then, they assessed the risk of bias. Pairwise meta-analysis and Bayesian network meta-analysis were conducted to estimate the effectiveness and ranking of the five electrical stimulation methods. Results A total of 33 trials with a final total of 2246 subjects were included in the analysis. By combining the comprehensive Rehabilitation Treatment (RT), the treatment effects of using five electrical stimulation methods were surperior to those of using RT only. In the meantime, RT+transcranial Direct Current Stimulation(tDCS) and RT+Functional Electrical Stimulation(FES) could be the optimal electric stimulation schemes for restoring lower limb motor function(SMD 8.35, 95%CI [3.05, 13.34]/ SMD 5.64, 95%CI [3.68, 7.56]), improving balance (SMD 9.80, 95%CI [0.67, 20.93]/ SMD 6.54, 95%CI [3.85, 10.95]) and activities of daily living(SMD 18.95, 95%CI [0.401, 36.9]/ SMD 15.47, 95%CI [7.89, 22.75]), and the treatment effects would be even better using RT+FES+tDCS combination. Conclusion tDCS and FES superior to other electrical stimulation methods based on RT in the treatment of lower limb dysfunction after stroke.